Sustainability in Self Build Housing in Rural Area of Kedah, Malaysia - Wan Mohamad, Wan Srihani; Ahmad, Yahaya (International Journal of Property Sciences (E-ISSN: 2229-8568), 2016)
Communities face enormous challenges as their social, economic, and environmental resources are depleted and destroyed. Sustainable development represents a holistic way to achieve recovery and enhances the quality of life for everyone in these communities. This concept can be addressed through the development of local assets to revitalise economies, limit waste and pollution, improve the status of disadvantaged people, conserve natural resources, and promote cooperation and efficiency. Among the steps to facilitate the planning and actions by these stakeholders and become effective agents in achieving sustainability is the employment of self help approach to build houses. This paper attempts to provide an overview of the use of self help housing as an avenue to assist home ownership leading to the creation of sustainable community. It further attempts to uncover the responses from the rural households in Kedah (Malaysia) towards the concept of self build housing through the introduction of a simplified prefabricated system and to gather responses on the usage of the system.It is found that majority of the respondents had given positive responses in that the self build components were easily assembled not withstanding that this system introduced a new method to construct a house.